Optimization of Zn/Al-Oxalate Hydrotalcite as an Environmentally Friendly Adsorbent for Dye Waste Processing - Dian Windy Dwiasi; Ely Setiawan; Aisyah Nur Izah; Arikunto Tegar Rizqian (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
Methylene blue is a synthetic dye commonly used in the textile industry. Methylene blue waste that is discharged into water bodies without treatment causes environmental pollution. One method of waste treatment is adsorption. Hydrotalcite is an anionic clay consisting of stacked positively charged layers, usually divalent (+2) and trivalent (+3) metal cations, and has anions between the layers. This study aims to determine the synthesis method of Zn/Al-Oxalate hydrotalcite, and its characterization results are compared with Zn/Al-NO3 hydrotalcite to determine the optimum conditions of Zn/Al-Oxalate hydrotalcite in adsorbing methylene blue dye and to determine the kinetic and isotherm models of adsorption. Zn/Al-Oxalate hydrotalcite was successfully synthesized by the coprecipitation method and continued with the hydrothermal process at a temperature of 120°C for 20 hours. Hydrotalcite Zn/Al-Oxalate was characterized using FTIR and XRD. The optimum condition of hydrotalcite Zn/Al-Oxalate in adsorbing methylene blue dye was carried out by the batch method at optimum pH 7, contact time 60 minutes, adsorbent weight 80 mg, and methylene blue concentration 20 mg/L. The adsorption kinetics of hydrotalcite Zn/Al-Oxalate in adsorbing methylene blue followed the pseudo-second-order model. with a value of R2 = 0.9996 and k = 0.2047 mg/g.min and the adsorption isotherm follows the Langmuir adsorption isotherm model R2 = 0.9904, qm = 19.8413 mg/g and kL = 2.913 L/mg.